Engineered Circular RNA CircmiR‐29b Attenuates Muscle Atrophy by Sponging MiR‐29b. Issue 7 (7th May 2022) - Li, Jin; Chen, Rui; Zheng, Yongjun; Yuan, Weilin; Yang, Tingting; Zhu, Xiaolan; Yan, Yuwei; Jin, Bing; Xu, Wanru; Zhang, Zhongrong; Li, Guoping; Gokulnath, Priyanka; et al.
Abstract: Muscle atrophy is commonly caused by various diseases but still lacks effective treatment in clinical practice. Here, an artificial circular RNA (circRNA) named circmiR‐29b, which is designed to be a molecular sponge for miR‐29b containing 12 imperfect bulged miR‐29b binding sites is constructed. CircmiR‐29b shows a favorable functional effect with respect to miR‐29b repression in a specific and drastic manner. CircmiR‐29b can protect against in vitro muscle atrophy induced by dexamethasone (Dex), angiotensin II (Ang II), and tumor necrosis factor alpha (TNF‐α). Besides, circmiR‐29b attenuates in vivo muscle atrophy induced by denervation, immobilization, and Ang II. More importantly, skeletal muscle specific gene therapy using circmiR‐29b is able to attenuate established muscle atrophy induced by spiral wire immobilization. This work has developed an engineered circmiR‐29b acting as an miR‐29b sponge, and offers a promising therapeutic tool to prevent muscle atrophy. Abstract : An engineered circular RNA, circmiR‐29b, which is designed to be a molecular sponge of miR‐29b is developed. CircmiR‐29b is effective in preventing muscle atrophy, as well as, treating established muscle atrophy.